Introducing STARDIS: An Open and Modular Stellar Spectral Synthesis Code - Joshua V. Shields; Wolfgang Kerzendorf; Isaac G. Smith; Tiago M. D. Pereira; Christian Vogl; Ryan Groneck; Andrew G. Fullard; Jaladh Singhal; Jing Lu; Christopher J. Fontes (The Astrophysical Journal)
We introduce a new 1D stellar spectral synthesis Python code called stardis . stardis is a modular, open-source radiative transfer code that is capable of spectral synthesis from near-UV to IR for FGK stars. We describe the structure, inputs, features, underlying physics, and assumptions of stardis , as well as the radiative transfer scheme implemented. To validate our code, we show spectral comparisons between stardis and korg with the same input atmospheric structure models, and we also compare qualitatively to phoenix for solar models. We find that stardis generally agrees with korg for solar models on the few-percent level or better, though the codes can diverge in the UV, with more extreme differences in cooler stars. stardis can be found at https://github.com/tardis-sn/stardis , and documentation can be found at https://tardis-sn.github.io/stardis/ .